2023
DOI: 10.1073/pnas.2219634120
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species are regulated by immune deficiency and Toll pathways in determining the host specificity of honeybee gut bacteria

Abstract: Host specificity is observed in gut symbionts of diverse animal lineages. But how hosts maintain symbionts while rejecting their close relatives remains elusive. We use eusocial bees and their codiversified gut bacteria to understand host regulation driving symbiotic specificity. The cross-inoculation of bumblebee Gilliamella induced higher prostaglandin in the honeybee gut, promoting a pronounced host response through immune deficiency (IMD) and Toll pathways. Gene silencing and vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Notably, downregulation of defensin-2 and apid-1 (AMP) gene expression can lead to pathogen intervention and death [25] to promote short-lived mechanisms in spring honey bees. Our results, especially the nine correlations in Nb compared to three correlations in Fb honey bees between ROS enzyme genes with innate immunity genes, support the findings of Guo et al that the regulatory function of the Imd and Toll pathways for ROS production is crucial in Nb honey bees [33], but not in Fb honey bees (Figure 6C-F). Overall, it additionally revealed the task-specificity of this pattern for Nb and Fb honey bees.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, downregulation of defensin-2 and apid-1 (AMP) gene expression can lead to pathogen intervention and death [25] to promote short-lived mechanisms in spring honey bees. Our results, especially the nine correlations in Nb compared to three correlations in Fb honey bees between ROS enzyme genes with innate immunity genes, support the findings of Guo et al that the regulatory function of the Imd and Toll pathways for ROS production is crucial in Nb honey bees [33], but not in Fb honey bees (Figure 6C-F). Overall, it additionally revealed the task-specificity of this pattern for Nb and Fb honey bees.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have demonstrated that defensin-1 plays a role in enhancing the antioxidant capacity of honey and other products derived from bees [81]. Research has shown its effectiveness in counteracting ROS and decreasing oxidative stress in different cellular and animal models [87,88]. Defensin-1 plays a crucial role in safeguarding cells and tissues against oxidative damage, which is commonly linked to aging, inflammation, and chronic diseases [87][88][89].…”
Section: Antioxidant Properties Of the Peptide Defensin-1: Final Remarksmentioning
confidence: 99%
“…Research has shown its effectiveness in counteracting ROS and decreasing oxidative stress in different cellular and animal models [87,88]. Defensin-1 plays a crucial role in safeguarding cells and tissues against oxidative damage, which is commonly linked to aging, inflammation, and chronic diseases [87][88][89]. It achieves this by neutralizing free radicals and preventing lipid peroxidation.…”
Section: Antioxidant Properties Of the Peptide Defensin-1: Final Remarksmentioning
confidence: 99%
“…Eusocial corbiculate bees, including honey bees, bumblebees, and stingless bees, harbor distinctive gut microbiota that are more similar among closely related bee species [122]. The exotic strain of the gut symbiont Gilliamella in honey bees induced higher prostaglandin (PG) production than the native strain, which increased the expression of genes in the IMD and Toll immune pathways [157]. These immune pathways then modulated dual oxidase (Duox) production and ROS generation to inhibit the non-native strain of Gilliamella.…”
Section: Immune Systemmentioning
confidence: 99%